ANALYSIS OF PRESSURE DISTRIBUTION TEST AND BEARING CAPACITY OF AIR BEARING BASED ON PARTITION ASSUMPTION - YANG ShaoHua; LONG Wei; PEI Hao (Jixie qiangdu)
Orifice throttle is a common way of throttling in the air static pressure guide rail,In order to study the gas film pressure distribution of the air static pressure guide rail,a gas thrust bearing gas film pressure distribution test bench was developed. In this paper,the orifice throttling is an example,based on the law of the gas film pressure decline,the gas film is divided into the pressure driven area and the Newton friction area. The gas flow pattern in the gas film support area is simulated by Fluent and the flow rate and pressure are calculated. The experimental results are in good agreement with the numerical analysis of the gas pressure distribution. It is concluded that the gas film is divided into the pressure driven area and the Newton friction zone along the length of the gas film,which verifies the validity of the pressure partition theory.